Paleo-biodegradation and hydrocarbon mixing in a major hybrid petroleum reservoir - Jaime Cesar; Omid H. Ardakani; Elizabeth Watt; Yishu Song; Andrew Kingston; Jason M. E. Ahad (Scientific Reports, 2023)
Abstract Some of the parental material for hydrocarbons produced from low-permeability reservoirs in Western Canada corresponds to thermal products from biodegraded oil. This has been proved by the occurrence of framboidal pyrite, which is often formed during microbial sulfate reduction (MSR). In addition, the identified pyrite framboids are associated with the presence of phosphorus (P). Phosphorus (as phosphate) is a key nutrient and energy carrier for sulfate-reducing bacteria. The pyrite-P assemblage occurs embedded in solid bitumen (thermal residue), which confirms that migrated hydrocarbons provided the environment for microbial growth. Molecular products of severe biodegradation such as 17-nortricyclic terpanes were also detected. Biodegradation effects have been masked not only by thermal degradation of biodegraded oil during maximum burial, but also due to hydrocarbon mixing with late gas-condensate charges. Suitable conditions for biodegradation (< 80 °C, basin uplift) occurred during the Early Cretaceous. The confirmation of paleo-biodegradation means that there was a significant hydrocarbon loss that we have not accounted for. Likewise, MSR and Early Cretaceous seawater sulfate might have played an important role in the generation of the hydrogen sulfide (H2S) detected today.